Digital piracy debunked: a short note on digital threats and intermediary liability - Giancarlo F. Frosio (Internet Policy Review, 2016)
In the last two decades, the industry has deployed endlessly the rhetoric of the "digital threat" in order to demand harsher measures against digital piracy. Recently, the "digital threat" discourse called for enhanced liability of online intermediaries, especially those whose platforms may be used to infringe copyright. This short paper shows that the "digital threat" discourse is based on shaky grounds. Two related arguments might run against this approach. First, market conditions might incentivise piracy. Additionally, there are raising doubts over the argument that piracy is a threat to creativity, especially in the digital environment. Overall, it may be hard to find a factual justification for policy decisions based on the "digital threat" discourse. In fact, digital technology seems not to have negatively affected the creation of new works. In contrast, an observation of the literature and quantitative analysis on point may suggest that digital piracy can be an opportunity for the cultural market. Finally, piracy may function as an innovation policy by forcing market players to innovate in response to a consumer demand that widespread piracy highlights.
Keywords: 300; Intermediary liability; Piracy; Copyright